2016
DOI: 10.1007/s00705-016-2812-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a porcine reproductive and respiratory syndrome virus-like-particle-based vaccine and evaluation of its immunogenicity in pigs

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is a leading cause of economic burden to the pork industry worldwide. The routinely used modified live PRRS virus vaccine (PRRS-MLV) induces clinical protection, but it has safety concerns. Therefore, in an attempt to develop a safe and protective inactivated PRRSV vaccine, we generated PRRS-virus-like-particles (PRRS-VLPs) containing the viral surface proteins GP5-GP4-GP3-GP2a-M or GP5-M using a novel baculovirus expression system. Our in vitro results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…However, the impressive mutability and recombination capacity and, therefore, genetic variability, of the virus resulted in incomplete clinical benefit of live or inactivated PRRS vaccines [9, 10]. Recent efforts to develop alternative vaccination methods, such as virus-like particles, replicon vectors, and a nonpathogenic porcine circovirus type 1 virus vector to induce a neutralizing response against purported neutralizing epitopes have yet to demonstrate immunological protective efficacy [1113]. …”
Section: Prrsv Neutralizing Antibodiesmentioning
confidence: 99%
“…However, the impressive mutability and recombination capacity and, therefore, genetic variability, of the virus resulted in incomplete clinical benefit of live or inactivated PRRS vaccines [9, 10]. Recent efforts to develop alternative vaccination methods, such as virus-like particles, replicon vectors, and a nonpathogenic porcine circovirus type 1 virus vector to induce a neutralizing response against purported neutralizing epitopes have yet to demonstrate immunological protective efficacy [1113]. …”
Section: Prrsv Neutralizing Antibodiesmentioning
confidence: 99%
“…Therefore, these three proteins likely play important roles in the assembly of virus particles for PRRSV, although other minor structural proteins including E (envelope protein), GP2, GP3, and GP4 (encoded by ORF 2, 3, and 4 respectively) may also contribute to the formation of infectious virus particles. A recent study has demonstrated a partial protection of PRRSV VLPs vaccine composed of five structural proteins including GP3, GP4, GP5, E, and M against homologous challenge when delivered together with PLGA nanoparticles [3]. In this study, we generated VLPs by expressing four PRRSV structural proteins including M, N, GP5, and E and assessed their immunogenicity and protective efficacy in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported the immunogenicity of PRRSV VLPs or chimera VLPs containing GP5 or GP5 and M proteins or the conserved protective epitopes of viral structural proteins in mice [19, 20, 26, 27]. Only one recent study described the partial protection against PRRSV in pigs immunized with PRRSV VLPs containing GP2, GP3, GP4, GP5 and M proteins [3]. More research is needed to fully explore the potential utility of VLPs in PRRSV vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…The GP5 protein and M protein have been shown to induce antibodies and high production of IFN- β (Binjawadagi et al, 2016). Here, we describe the construction of JEV replicons and use JEV replicon vectors expressing the PRRSV GP5 and M proteins as a bivalent seedlings vaccine.…”
Section: Discussionmentioning
confidence: 99%